The Law of Ritual Slaughter and the Principle of Religious Equality - Gliszczyńska-Grabias, Aleksandra (Journal of law, religion and state, 2016)
In December 2014, the Polish Constitutional Tribunal struck down as unconstitutional a statute that prohibited all animal slaughter conducted without prior stunning. The Tribunal found this law contrary to Polish (and European) provisions regarding freedom of exercise of religion. In the present paper, we critically analyze the judgment through the lens of the general principle of religious equality. Considering other European cases involving ritual slaughter, as well as a landmark us case on the matter, we propose a template for the discussion of equality in religious matters, based on a distinction between two formulas: “substantive” equality, which requires accommodation of religious requirements and often calls for exemptions from general rules; and “formal” equality, which calls for the equal application of general moral standards to all religious and non-religious practices. We conclude that a “formal” conception is also based on substantive moral considerations about the priority of some general moral requirements over those demanded by particular religious practices.